2000
DOI: 10.1021/ma0005670
|View full text |Cite
|
Sign up to set email alerts
|

A Family of Electroluminescent Silyl-Substituted Poly(p-phenylenevinylene)s:  Synthesis, Characterization, and Structure−Property Relationships

Abstract: A series of intense photoluminescent (PL) polymers containing silyl groups with chain length from C1 to C18 has been successfully synthesized through polycondensation reaction. Introducing silyl groups into a conjugated polymer affords the polymer good processability, amorphousness, good film-forming ability, and sharp emission. A systematic analysis of this series of polymers indicates that increasing the side chain length of the polymers will slightly lower the thermal stability while increasing the molecula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(138 citation statements)
references
References 52 publications
4
133
1
Order By: Relevance
“…These properties optical and electrical of polyaniline widen his application in several estate such as electronics devices (organo semi conductors, transistors),batteries and combustible piles .In many articles, preparation of polyaniline (PANI) soluble has been subjected [2] ,this very day, polymerization of aniline in montmorillonite(layered solid) by chemical methods have been reported [3]. The solubilization [4] of polyaniline is important parameter for studding, this physical propertie depend on the route of the synthesis of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…These properties optical and electrical of polyaniline widen his application in several estate such as electronics devices (organo semi conductors, transistors),batteries and combustible piles .In many articles, preparation of polyaniline (PANI) soluble has been subjected [2] ,this very day, polymerization of aniline in montmorillonite(layered solid) by chemical methods have been reported [3]. The solubilization [4] of polyaniline is important parameter for studding, this physical propertie depend on the route of the synthesis of polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The CV band-gap of polymer PPV-BD is 2.40 eV is slightly larger than its optical band. The discrepancy of values lies within the range of errors, and this discrepancy is probably due to interface barrier for charge injection [34,35].…”
Section: Electrochemical Propertiesmentioning
confidence: 54%
“…Huang et al reported that silylsubstituted PPVs have few structural defects in their polymer chains, and that the silyl groups contribute to the satisfactory solubility of these polymers, because of the larger atomic size of Si compared to C and O, as well as the longer bond length of Si-C compared to C-C and C-O [12]. The molecular weights of the polymers were measured by gel permeation chromatography, using THF as eluent, and polystyrene as standard.…”
Section: Resultsmentioning
confidence: 99%